Saving and growth in an open economy - Iris Claus; David Haugh; Grant Scobie; Jonas Tornquist (New Zealand Government, The Treasury, 2001)
Concern has been raised by an apparent lack of saving in New Zealand. It is often argued that policies which foster savings are important, as higher savings will contribute to higher economic growth. This paper investigates the link between saving, investment and growth. In particular, it focuses on issues potentially important in an open economy such as New Zealand. Theory predicts that increased total saving will lead to higher investment and output. In an open economy, total saving comprises saving by domestic agents (government, firms and households) plus foreign saving. Diversified portfolios, large inflows of foreign investment into New Zealand and investment rates comparable to those in other OECD countries suggest that New Zealand, so far, has been able to access foreign saving to meet investment demands. Domestic saving does not appear to have constrained investment and hence growth.
Keywords: E21; E22; O16; 330; Economic growth; saving; capital flows